Brother of Jesus, Friend of God: Studies in the Letter of James. By Luke Timothy Johnson. Pp. x + 290. Grand Rapids, MI: William B. Eerdmans, 2004. isbn 0 8028 0986 3. Paper £21.99/30 - Painter, John (The journal of theological studies, 2005)
Luke Timothy Johnson has produced numerous significant publications in the two decades during which most of the essays contained in this volume were first published. The earliest appeared in 1982, while two of the chapters were written especially for this volume. Given the spread of time over which the book was written, the volume hangs together very well. As the subtitle notes, it contains studies in the Letter of James. The earlier essays were written while Johnson was preparing his Anchor Bible commentary on The Letter of James, which was published in 1995. Given the more focused nature of the studies in the present volume, it supplements and extends the range of the commentary rather well.